Augmentation of Antipsychotic Medications with Low-Dose Clozapine in Treatment-Resistant Schizophrenia—Case Reports and Discussion - Zoe Harrison; Owen Haeney; William Brereton (Case Reports in Psychiatry)
Treatment resistance in schizophrenia is often encountered in clinical practice, with clozapine usually recommended as the appropriate therapy. However, where clozapine proves ineffective or cannot be tolerated due to side effects, treatment options are limited. In patients within forensic mental health services, residual symptomatology often presents a barrier to discharge and can have lasting effects on prospects for rehabilitation as well as risk to self and others. This paper presents a review of the relevant literature and three cases of a novel approach, utilising clozapine in doses usually considered subtherapeutic, in combination with the primary antipsychotic treatment. In all three patients, it improved clinical efficacy as well as tolerability, resulting in improvement that allowed discharge from the forensic hospital.